An Implementation Science Approach to Promote Optimal Implementation, Adoption, Use, and Spread of Continuous Clinical Monitoring System Technology. Issue 1 (January 2021) - Dykes, Patricia C.; Lowenthal, Graham; Faris, Ann; Leonard, Michelle Waters; Hack, Robin; Harding, Deborah; Huffman WHNP, Carolyn; Hurley, Ann; An, Perry
Abstract : Objectives: This study aimed to apply implementation science tenets to guide the deployment and use of in-hospital Clinical Monitoring System Technology (CMST) and to develop a toolkit to promote optimal implementation, adoption, use, and spread of CMST. Methods: Six steps were carried out to (1) establish leadership support; (2) identify, educate, and sustain champions; (3) enlist clinical staff users to learn barriers and facilitators; (4) examine initial qualitative data from 11 clinician group interviews; (5) validate barriers/facilitators to CMST use and toolkit content; and (6) propose a toolkit to promote utilization. Clinical Monitoring System Technology output before and after implementation were compared. Results: The top 3 barriers to effective CMST use were as follows: (1) inadequate education/training/support, (2) clinical workflow challenges, and (3) lack of communication. Facilitators to CMST implementation and adoption included the following: (1) providing comprehensive and consistent CMST education, (2) presenting evidence early and often, (3) tailoring device and usage expectations to individual environments, and (4) providing regular feedback about progress. Empirical data drove the development of a CMST implementation toolkit covering 6 areas: (1) why, (2) readiness, (3) readiness and implementation, (4) patient/family introduction, (5) champions, (6) care team saves, and (7) troubleshooting. Clinical Monitoring System Technology positively impacted failure to rescue events. Monthly median cardiac alert responses decreased from 30 to 3.64 minutes (87.9%), and respiratory alert responses decreased from 26 to 4.85 minutes (81.4%). Conclusions: Using implementation science tenets to concurrently guide deployment and study performance of 2 CMST devices and impact on workload was effective for both learning CMST efficacy at 2 hospital systems and developing a toolkit to promote optimal implementation, adoption, use, and spread. Abstract : Supplemental digital content is available in the text.